2013
DOI: 10.1016/j.jtherbio.2012.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Trade-off between thermal sensitivity, hypoxia tolerance and growth in fish

Abstract: International audienceOne outcome of contemporary climate trends is that the involvement of hypoxia and heat tolerance in determining individual fitness will increase in many fish populations. Large fish are believed to be more tolerant to hypoxia than small fish (Nilsson and Östlund-Nilsson, 2008) whereas thermal sensitivity is thought to decrease with body size (Clark et al., 2008). To better understand the bases of inter-individual variation in environmental adaptation performance, the current study examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 62 publications
(67 citation statements)
references
References 61 publications
3
61
1
Order By: Relevance
“…For example, they can induce difficulty in avoiding predators or catching prey. There is also a link between growth and the ability to face environmental stress: it has been demonstrated that larger fish are more tolerant to hypoxia episodes than smaller ones (Clark et al, 2008;Roze et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…For example, they can induce difficulty in avoiding predators or catching prey. There is also a link between growth and the ability to face environmental stress: it has been demonstrated that larger fish are more tolerant to hypoxia episodes than smaller ones (Clark et al, 2008;Roze et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The method of this challenge test was previously described [41, 42]. Briefly, the rearing water was deprived of oxygen by bubbling nitrogen gas in the tank, under constant monitoring of dissolved O 2 .…”
Section: Methodsmentioning
confidence: 99%
“…It is a classic adaptive response to stress. The decrease in the sediment reworking behavior could then result energetic trade-offs between activity, reproduction, growth, and maintenance (see among others Handy et al 1999;Marchand et al 2004;Roze et al 2013). …”
Section: Energetic Strategy and Multistress Effectsmentioning
confidence: 99%